Money and Emerging Adults: A Glimpse into the Lives of College Couples’ Financial Management Practices - Jennifer K Rea; Virginia S Zuiker; Tai J Mendenhall (Journal of Financial Therapy, 2016)
Being in a romantic relationship is a transition that many college students enter while earning a college degree. Twenty-four students between the ages of 19 to 29 years old who self-identified as being in a committed relationship participated in this study. They completed an online survey that included both quantitative and qualitative (open-ended) questions pertaining to money management practices. Key findings suggest that participants believe in communicating about their individual and combined finances so as to prevent or solve financial challenges. They also discussed the importance of having similar perspectives about financial values within their relationship. Financial therapists, counselors, and educators working with the college student populations should be aware of the issues couples in committed relationships face, and should tailor their money management programming with this in mind.
Keywords: college students; committed relationships; money management; young couples